The study of flame retardancy and thermal properties of seacell® fabrics - (:unkn) unknown (My University, 2013)
Bu çalışmada medikal ve ekolojik olarak bilinen SeaCell®active and SeaCell®pure ipliklerden üretilen kumaşların güç tutuşurluk özellikleri araştırılmıştır. SeaCell® staple elyaftan üretilen ipliklerden kumaşlar oluşturularak boyama sonrası SeaCell®active ve SeaCell®pure kumaşlara fosfor inorganik sinerjik ve organofosfor bileşikleri (N-hidroksimetil-3-dimetilfosfonopropionamid) maddeleri kullanılarak güç tutuşurluk bitim işlemi uygulandı. Daha sonra yıkama öncesi ve yıkama sonrası güç tutuşurluk özellikleri incelendi. Buna ek olarak termal özellikleri ve güç tutuşurluk maddelerinin etkilerine bakıldı. Güç tutuşurluk maddeleri uygulanan SeaCell®active and SeaCell®pure kumaşların Limit Oksijen İndeksi (LOI), diferansiyel taramalı kalorimetri (DSC) ve termogravimetrik analiz yöntemleri kullanılarak yapısal değişikler araştırıldı. %100 SeaCell® kumaşlara uygulanan güç tutuşurluk işlemi sonrası, fosfor inorganik sinerjik maddesi ile LOI değeri %31, 15 yıkama sonunda ise LOI değeri %20 olarak elde edilmiştir. N-hidroksimetil-3-dimetilfosfonopropionamid maddesi ile yapılan uygulamada ise %28 LOI değeri elde edilirken 15 yıkama sonrasında %26 olarak tespit edilmiştir. DSC ve TGA termogramların birbirlerini desteklediği görülmüştür.

In this study, the properties of flame retardant woven fabrics produced from the SeaCell®active and SeaCell®pure yarns, which are known as ecological and medical textile materials, were investigated. The yarns were produced from SeaCell® stapel fibres and then were woven into fabric. After dyeing, the fabrics flame retardants which has phosphorus inorganic synergism and organophosphorus compounds (N-hydroxymethyl-3-dimethylphosphonopropionamide), were applied to the the SeaCell®active and SeaCell®pure fabrics, and later the flame retardant properties were determined before and after washing processes. In addition to that, thermal properties of the fabrics and the effects of flame retardants were studied. The flammability of the flame retardant treated SeaCell®active and SeaCell®pure were characterized by using limiting oxygen index (LOI). Structural changes of the treated SeaCell®active and SeaCell®pure and the compounds were carried out by using thermal analysis methods of differential scanning calorimeter (DSC) and thermogravimetric analysis (TGA). After flame retardant treatment on the 100% SeaCell® fabrics, the LOI value of the sample with phosphorus inorganic synergism reached to 31 % and after 15 successive washing the LOI value was 20%. On the other hand, while obtaining 28% LOI value with the application of the N-hydroxymethyl-3- dimethylphosphonopropionamide after 15 successive washing this was achieved only 26%. It was also observed that both DSC and TGA thermograms were verifies their results.
Seacell® kumaşların termal özellikleri ve güç tutuşurluk özelliklerinin incelenmesi
Keywords: Malzeme Bilimleri, Tekstil